2010
DOI: 10.1111/j.1472-8206.2010.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Doping and musculoskeletal system: short‐term and long‐lasting effects of doping agents

Abstract: Doping is a problem that has plagued the world of competition and sports for ages. Even before the dawn of Olympic history in ancient Greece, competitors have looked for artificial means to improve athletic performance. Since ancient times, athletes have attempted to gain an unfair competitive advantage through the use of doping substances. A Prohibited List of doping substances and methods banned in sports is published yearly by the World Anti-Doping Agency. Among the substances included are steroidal and pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 266 publications
(531 reference statements)
0
22
0
Order By: Relevance
“…For example, some resources explain how diuretics are used for weight loss (which could be perceived as a benefit for some athletes) but also can result in dehydration and fatigue (Nikolopoulos et al, 2011). In this case, the benefits of using diuretics is considered non-framed because it did not match our operational definition of either a gain-or loss-framed message, but the consequences of taking diuretics was classified as loss-framed.…”
Section: Coding Manualmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some resources explain how diuretics are used for weight loss (which could be perceived as a benefit for some athletes) but also can result in dehydration and fatigue (Nikolopoulos et al, 2011). In this case, the benefits of using diuretics is considered non-framed because it did not match our operational definition of either a gain-or loss-framed message, but the consequences of taking diuretics was classified as loss-framed.…”
Section: Coding Manualmentioning
confidence: 99%
“…Diuretics, typically used for weight loss, can cause excessive water loss, depleting the body of essential minerals, which can lead to muscle cramps and weakness. Narcotics, marijuana, and other pain-relieving drugs allow athletes to push through the pain but can lead to longer lasting injuries (Nikolopoulos, Spiliopoulou, & Theocharis, 2011). In addition to these side effects, qualitative research has shown that athletes who have tested positive or have admitted to using PES have a great deal of guilt and shame related to their PES use (Kirby, Moran, & Guerin, 2011).…”
mentioning
confidence: 99%
“…Some athletes use glucocorticoids to improve their performance inducing mobilization of fatty acids, amino acids and stimulate gluconeogenesis, although many of them use it to reduce pain and fatigue, not knowing the side effects in the long term (Nikolopoulos, Spiliopoulou, Theocharis, 2010). For example, glucocorticoids are administered for the treatment of chronic tendinitis and tendon injuries.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…There are many studies suggesting that caffeine improves power and endurance compared to placebo or other supplements [26,29,35,54,57,81]. A moderate dose of caffeine significantly improves performance DOI 10.18502/ajne.v2i1.1242…”
Section: Introductionmentioning
confidence: 99%